STRIVE FOR POWER IN THE GODFATHER MOVIE - AIRLANGGA, ALDINO (Jurnal Ilmiah Mahasiswa FIB, 2014)
Airlangga,  Aldino.2013.  Strive  for  power  in  The  Godfather  Movie.  Study progam of English Universitas Brawijaya.Supervisor: Fredy Nugroho Setiawan; Co-Supervisor: Winda Candra Hantari.Keyword:  Strive  for  power,  Individual  Psychology,  Alfred  Adler,  Michael Corleone, Vito Corleone, The Godfather MovieThe Godfather presents  about  the  life of  Italian American mafia  family  in the late 1941. The movie focuses on Vito Corleone, a feared Don and a reasonable man from Corleone family. Don in Italian culture is like a noble man or someone who  is  respected by most people. While in mafioso culture Don  is  like a boss or man  that  have  right  to  command  in  criminal  organization,  or  they  called  “La Famiglia” (The Family). After Vito retires from family business his son Michael Corleone takes the control of family and wants to bring Corleone family  stronger, more  feared  and  become  unbeatable.  This  is  a  story  about  an  absolute  power, money and man that control everything behind the scene like a puppet master. This study discusses about  the strive for power as an approach  that  is used in  the  movie. Michael  and  Vito  Corleone  strive  their  power  and  inlfuence  in different way but  they have  the  same goal. This  study  tries  to  reveal  the  reason why  they  do  this  and  how  the  process  of  striving  power  according  to  strive  for power theory from Alfred Adler book Individual Psychology.